INDICATION-BASED TYPICAL DIAGNOSTIC REFERENCE LEVEL FOR BARIUM SWALLOW EXAMINATION AT THREE CENTRES IN KAMPALA, UGANDA, A CROSS-SECTIONAL STUDY. - SSEWAGUDE, KIZITO; Musisi, Alen; Nakatudde, Rebecca; Ameda , Faith; Nabbosa , Valeria; Terebu, Joseph; Erem, Geoffrey (Student’s Journal of Health Research Africa, 2024)
Introduction The reduction in utilization of barium examinations is attributable to excessive exposure to ionizing radiations but also due to more advanced imaging modalities. Diagnostic Reference Levels (DRLs) are employed in identifying unusually high radiation doses so that corrective action can be taken. DRLs are not established in many African countries, Uganda inclusive. Objective To determine the Typical Diagnostic Reference Level for barium swallow examination of patients with dysphagia at three centers in Kampala, Uganda. Methodology It was a cross-sectional, descriptive, and analytical study. It involved 90 adult patients with dysphagia, who were consecutively recruited and underwent barium swallow examination. The exposure parameters were recorded and used to calculate radiation doses, from which the 50th percentile was derived as the Typical diagnostic reference level. Results The overall mean; kilovoltage (69.4 kilovolts), Fluoroscopic time (2.5 minutes), and outcome dose area product (6.4 Gycm2) had significant differences between the 3 centers (p-value =0.001,0.001,0.006) respectively. The overall mean current was 27.1mAs, without significant differences between the 3 centers (p = 0.0197). There was a statistically significant (p = 0.002) positive relationship between radiation doses and BMI. There was a negative relationship between radiation doses and age. The median outcome dose area product was 5.7Gycm2which was the Indication based Typical DRL for the barium swallow examination. Conclusion There were significant differences in exposure factors between centers and a significant positive relationship between radiation doses and BMI. The Typical DRL value for barium swallow examination was 5.7Gycm2. Recommendation I recommend that all imaging centers adopt the established typical DRL, with a regular review of exposure factors in order to optimize radiation exposure.